Pengaruh Pemberian Kunyit Asam Terhadap Penurunan Dismenorea Pada Remaja - Maera Kartika Sari; Winarni Winarni (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background : Adolescence is a period of transition from children to adults which is accompanied by growth and physical changes, including the growth of the reproductive organs. The maturity of the female reproductive organs is marked by the arrival of menstruation, one of the problems during menstruation experienced by young women is dysmenorrhea. Dysmenorrhea is usually concentrated in the lower abdomen that occurs before and during menstruation caused by uterine contractions. The management of dysmenorrhea can use non-pharmacological therapy, one of which is by giving tamarind turmeric drink. Tamarind contains curcumin and anthocyanins which inhibit cyclooxygenase, thereby reducing inflammation and inhibiting uterine contractions. The content of curcumenol in turmeric acts as an analgesic agent that can reduce the production of prostaglandins. Research Methods: This study used quantitative research with the pre-experimental one group pretest posttest method. The population in this study were 35 teenagers. The sampling technique used was simple random sampling, with a sample of 21 adolescents who experienced dysmenorrhea in May-July in Pelem Hamlet. Data collection used a pain scale observation sheet, namely the NRS (Numeric Rating Scale) before and after administration of tamarind turmeric. Data were analyzed using the Wilcoxon Signed Rank Test. Results: Based on the analysis test using the Wilcoxon Signed Rank Test, a significance value of 0.00 (p <0.05) was obtained, which means that Ha was accepted. Conclusion: There are differences in the degree of pain in dysmenorrhea before and after administration of tamarind turmeric, so it can be concluded that there is an effect of tamarind administration on dysmenorrhea in young women. Keywords: Dysmenorrhea, Tamarind Turmeric, Adolescents Background : Adolescence is a period of transition from children to adults which is accompanied by growth and physical changes, including the growth of the reproductive organs. The maturity of the female reproductive organs is marked by the arrival of menstruation, one of the problems during menstruation experienced by young women is dysmenorrhea. Dysmenorrhea is usually concentrated in the lower abdomen that occurs before and during menstruation caused by uterine contractions. The management of dysmenorrhea can use non-pharmacological therapy, one of which is by giving tamarind turmeric drink. Tamarind contains curcumin and anthocyanins which inhibit cyclooxygenase, thereby reducing inflammation and inhibiting uterine contractions. The content of curcumenol in turmeric acts as an analgesic agent that can reduce the production of prostaglandins. Research Methods: This study used quantitative research with the pre-experimental one group pretest posttest method. The population in this study were 35 teenagers. The sampling technique used was simple random sampling, with a sample of 21 adolescents who experienced dysmenorrhea in May-July in Pelem Hamlet. Data collection used a pain scale observation sheet, namely the NRS (Numeric Rating Scale) before and after administration of tamarind turmeric. Data were analyzed using the Wilcoxon Signed Rank Test. Results: Based on the analysis test using the Wilcoxon Signed Rank Test, a significance value of 0.00 (p <0.05) was obtained, which means that Ha was accepted. Conclusion: There are differences in the degree of pain in dysmenorrhea before and after administration of tamarind turmeric, so it can be concluded that there is an effect of tamarind administration on dysmenorrhea in young women. Keywords: Dysmenorrhea, Tamarind Turmeric, Adolescents